A genetic roadmap of pancreatic cancer: still evolving. Issue 12 (9th October 2017) - Notta, Faiyaz; Hahn, Stephan A; Real, Francisco X
Abstract : A diagnosis of pancreatic ductal adenocarcinoma (PDA) is often fatal. PDA is widely recognised as one of the 'incurable cancers' because therapies against this tumour type are generally ineffective. The fatal nature of this tumour is due to its aggressive clinical course. Pancreatic cancer commonly presents at the metastatic stage; even in cases where tumours are localised to the pancreas at diagnosis, metastatic seeds have often been invariably been spawned off, frustrating surgical attempts to cure the cancer. The key principles of pancreatic cancer mutational development were outlined nearly two decades ago using the genetics of precursor lesions to position the various stages of tumour progression. Since then, there has been a cavalcade of new data. How these recent studies impact the classical perceptions of pancreatic cancer development is a work in progress. Given that significant improvements in patient outcomes are not in sight for this disease, it is likely that broadening the current perspectives and acquiring deeper biological insights into the morphogenetic route of tumour development will be needed to foster new strategies for more effective cancer control.